1990
DOI: 10.1016/0042-6989(90)90058-s
|View full text |Cite
|
Sign up to set email alerts
|

The visible persistence of stimuli in stroboscopic motion

Abstract: Abstract-This paper reports an improved paradigm to measure visible persistence. The stimulus is a pair of lines stroboscopically displayed in successive positions moving in opposite directions. The subjects' judgement of simultaneous appearance of all the presented lines is used to estimate visible persistence. This paradigm permitted independent manipulation of spatial and temporal stimulus separations in linear motion. The resulting estimates of visible persistence increase with spatial separation up to 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…This finding suggested that motion-detection mechanisms were not critical for deblurring moving stimuli, and that lateral inhibition interacting across space and time inhibited persisting representations of past stimuli. Farrell, Pavel, and Sperling (1990) showed similar results using stimuli that moved in apparent motion. They also developed a descriptive model of visual persistence that outlined how lateral inhibition from a new stimulus affects the decay of old stimulus representations.…”
mentioning
confidence: 53%
“…This finding suggested that motion-detection mechanisms were not critical for deblurring moving stimuli, and that lateral inhibition interacting across space and time inhibited persisting representations of past stimuli. Farrell, Pavel, and Sperling (1990) showed similar results using stimuli that moved in apparent motion. They also developed a descriptive model of visual persistence that outlined how lateral inhibition from a new stimulus affects the decay of old stimulus representations.…”
mentioning
confidence: 53%
“…Figure 4a from Farrell,Pavd,81. Sperling (1990) shows that the influence of a rnask on the pm·sistence of a target deperHls on the spatial distance between the stirnuli, with closer masks decreasing the persistence of the target. Other studies (Farrell, 1984; DiLollo 81.…”
Section: Pamdo:cicai Incrcasc Of J!ctsisicncc Of Iitusory Conlonrsmentioning
confidence: 99%
“…Francis, Grossberg, and Mingolla (1994) quantitatively sirnulatcd the BC:S model and showed that a key process governing the persistence of visual percepts is the tirne taken to reset a segrnentation. 'fhis analysis explained characteristics of illusory contour persistence (Meyer and Ming, 1988), effects of orientation-specific adaptation (Meyer, Lawson, and Cohen, 1975), spatial rnasking (Farrell, Pavel, and Sperling, 1990), and inverse relationships between persistence and stimulus lUJninance and duration (Bowen,Pola,and !Vlatin,1.974). Francis (1994) simulated the rnoclcl to explain relationships between persistence and interstimulus intervals of rnasking stirnuli (Castet,199·1).…”
Section: Introductionmentioning
confidence: 99%